Colossal dielectric behavior in Cex(In0.5+Nb0.5)1-xO2 ceramics. Issue 4 (15th February 2023) - Li, Tiantian; Cao, Wenjun; Wang, Jinsong; Zhang, Yingtang; Wang, Chunchang
Abstract: (In + Nb) co-doped Ce x (In0.5 +Nb0.5 )1- x O2 (with x  = 0, 0.005, 0.05, and 0.1) ceramics were prepared by conventional solid-state method. Dielectric properties of the ceramics were examined between 3 and 475 K and 10 2 and 10 6  Hz. All of the doped samples exhibit colossal permittivity (CP) behavior. Among them, the CP behavior of the sample with x  = 0.005 possesses the best frequency stability. Two thermally activated relaxations contribute to CP behavior. The low-temperature relaxation (R1) is a polaron relaxation caused by electron hopping between Ce 3+ and Ce 4+ ions. The high-temperature relaxation (R2) is a dipole relaxation caused by oxygen-vacancy-dopant defect pair.